2021
DOI: 10.3389/fcell.2021.631931
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase 2-Induced Cancer-Associated Fibroblasts Promote Hepatocellular Carcinoma Progression via Inhibition of Apoptosis and Induction of Epithelial-to-Mesenchymal Transition

Abstract: BackgroundSulfatase 2 (SULF2) removes the 6-O-sulfate groups from heparan sulfate proteoglycans (HSPG) and consequently alters the binding sites for various signaling molecules. Here, we elucidated the role of SULF2 in the differentiation of hepatic stellate cells (HSCs) into carcinoma-associated fibroblasts (CAFs) in the hepatocellular carcinoma (HCC) microenvironment and the mechanism underlying CAF-mediated HCC growth.MethodsThe clinical relevance of SULF2 and CAFs was examined using in silico and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…It is possible that a reduction in the number of CAFs in tumors by NIK knockdown contributes to the decline in the antiapoptotic potency of cancer cells. CXCL12/SDF-1 secreted by CAFs contributes to tumor growth and anti-apoptosis in cancer cells via CXCR4 39,40 . Indeed, the expression of CXCR4 was reduced in NIK knockdown cells; thus, there was a deficiency in the positive feedback through this paracrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a reduction in the number of CAFs in tumors by NIK knockdown contributes to the decline in the antiapoptotic potency of cancer cells. CXCL12/SDF-1 secreted by CAFs contributes to tumor growth and anti-apoptosis in cancer cells via CXCR4 39,40 . Indeed, the expression of CXCR4 was reduced in NIK knockdown cells; thus, there was a deficiency in the positive feedback through this paracrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…So chrysin antiproliferative action against GC cells might also be attributed to the suppression of SULF2. Inhibitors of SULFs are under study 12 , and, once these have been developed to the stage where they are suitable for cell-based and preferably in vivo studies, the therapeutic potential of SULF2 inhibition can be explored. It is possible that such compounds could counteract the effect of SULF2 by sequestering growth factors released in the extracellular and pericellular space 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the TGF-β/SMAD pathway induces type I and III collagen expression in human HSC line LX2. It has been confirmed that SULF2 expressed by HCC cells can induce HSCs into CAFs through the TGF-β/SMAD3 pathway, which may further inhibit apoptosis and promote EMT of HCC cells via the SDF-1/CXCR4-related signaling pathway ( 20 ). p300 acetyltransferase promotes TGF-β-stimulated HSC activation by both cytoplasm-to-nucleus shuttle for SMAD2/3-tafazzin (TAZ) and histone acetylation mechanisms ( 26 ).…”
Section: The Activation Of Cafs In the Premalignant Microenvironment Of Hccmentioning
confidence: 99%
“…Quiescent hepatic stellate cells (HSCs) and other normal fibroblasts suppress malignant cell growth via contact inhibition (18). While under liver injury, the inflammatory factors including sulfatase (SULF)-2, transforming growth factor (TGF)-b, CXCL6, and CXCR4 educate normal fibroblasts and other relevant cells toward CAFs (20)(21)(22) and increase the expression of CAF markers such as a-smooth muscle actin (SMA), FAP, vimentin, collagen, and fibroblast specific protein (FSP)-1 (23). The mechanisms for CAF activation are summarized in Figure 1.…”
Section: The Activation Of Cafs In the Premalignant Microenvironment Of Hccmentioning
confidence: 99%